“Utilización del hongo Pleurotus eryngii en la biodegradación de tres residuos de cosecha para la obtención de abonos orgánicos en la zona de Mocache”. - Mendoza Veliz Denisse Juleidy (2020)
The present research work aimed to evaluate the use of the Pleurotus eryngii fungus in the biodegradation of three crop residues to obtain organic fertilizers in the Mocache area. The multiplication of the inoculum was carried out in the Microbiology laboratory of the “La María” campus. A completely randomized design (DCA) was used with four treatments and four repetitions, each repetition was made up of one kg of substrate, for a total of 32 experimental units; T1: 100% corn husk + P. eryngii, T2: 100% rice husk + P. eryngii, T3: 100% peanut husk + P. eryngii, T4: mixture of 33.33% peanut husk + straw rice 33.33% + corn pan 33.33+ P. eryngii. The variables studied were the following: Biodegradation rate (TB), NPK, Organic Matter and initial and final pH. For the statistical analysis of the data, the analysis of variance was used and for comparisons of means, the Tukey test was used at 5% probability. The analysis of the results was carried out with the statistical package InfoStat. Biodegraded substrates were evaluated, obtaining as results that treatment1 (100% corn pan + P. eryngii) presented the best results for Biodegradation rate with (45.25%), nitrogen (0.5%), phosphorus (0.10%), potassium (0.75%), Organic Matter (35%), initial and final pH (6.94) (6.83) respectively. However, although it has presented the most favorable results in NP, it does not reach the minimum percentages for these variables, ranging from 1% nitrogen and 0.15% phosphorus. Therefore, the application of the fungus should be studied in a different waste from those used in the research and a longer biodegradation time of the substrates. Keywords: Biodegradation, organic compost, Pleurotus eryngii